2017
DOI: 10.1007/s00381-017-3550-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cerebellar giant cavernous malformation: case report and review of literature

Abstract: Cerebellar GCMs in children are symptomatic lesions, which prompt immediate surgical treatment. These are rare lesions, which can radiologically and clinically mimic a tumor with bleed, having to be considered in the differential diagnosis of neoplastic lesions. Cerebellar GCMs might be suspected in the presence of large hemorrhagic intra-axial mass with "bubbles of blood," multi-cystic appearance, surrounded by hemosiderin ring, fluid-fluid levels, and accompanying edema-mass effect. Careful radiological stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Although bleeding from a cavernoma is expected in the third and fourth decades of life, bleeding in GCs is more likely to occur in small children 5,10,11 , as well as at the age similar to our patient 15 . Localization was typical, as the majority of GCs found in the literature were located in the frontoparietal region 3,6 .…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Although bleeding from a cavernoma is expected in the third and fourth decades of life, bleeding in GCs is more likely to occur in small children 5,10,11 , as well as at the age similar to our patient 15 . Localization was typical, as the majority of GCs found in the literature were located in the frontoparietal region 3,6 .…”
Section: Discussionsupporting
confidence: 46%
“…Cavernomas (cavernous angiomas, hemangiomas) are benign, clearly defined, angiographically occult vascular malformations of the central nervous system, which are composed of vascular channels lined by one-layer endothelium separated by matrix made of collagenous tissue and smooth muscles [1][2][3] . Their prevalence ranges from 0.5% to 1% in the general population, and they account for 5%-15% of all intracranial vascular malformations [3][4][5][6][7][8][9][10] . They can be from a few millimeters to a few centimeters in size, usually smaller than 3 cm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 GCMs in children, however, have an increased hemorrhage risk and are more aggressive compared with those in adults, implying distinct, age-related biological behaviors. 19 To the best of our knowledge, GCMs have never before been detected incidentally or reported as asymptomatic. 4 Sansone et al reported a 72-year-old woman with metastatic breast carcinoma who had a dumbbell-shaped cavernous lesion in the pituitary region that was detected incidentally on post-mortem examination.…”
Section: Discussionmentioning
confidence: 92%
“…The surgical resection is currently seen as the best therapy available for symptomatic cases 14 . In large CM, due to the lesion size, the patient will invariably become symptomatic, making surgical treatment necessary regardless of the presence of symptoms [15][16][17] .…”
Section: Introduction Case Presentationmentioning
confidence: 99%